Anatomy of the tibial nerve in relation to the tarsal tunnel: A cadaveric study. Issue 8 (December 2022) - Mattos, Ivan; Ubillus, Hugo A.; Campos, Gustavo; Soares, Sergio; Azam, Mohammad T.; Oliva, Xavier Martin; Kennedy, John G.
Abstract: Background: Tarsal tunnel syndrome (TTS) is typically caused by an anatomical variant or mechanical compression of the tibial nerve (TN) with variable success after surgical treatment. Method: 40 lower-leg specimens were obtained. Dissections were appropriately conducted. Extremities were prepared under formaldehyde solution. The tibial nerve and branches were dissected for measurements and various characteristics. Results: The flexor retinaculum had a denser consistency in 22.5% of the cases and the average length was 51.9 mm. The flexor retinaculum as an independent structure was absent and 77.2% of cases as an undistinguished extension of the crural fascia. The lateral plantar nerve (LPN) and abductor digiti minimi (ADM) nerve shared same origin in 80% of cases, 34.5% bifurcated proximal to the DM (Dellon-McKinnon malleolar-calcaneal line) line 31.2% distally and 34.3% at the same level. Conclusion: Understanding the tibial nerve anatomy will allow us to adapt our surgical technique to improve the treatment of this recurrent pathology. Tarsal tunnel syndrome Tibial nerve Crural Fascia Malleolar-calcaneal line